Caracterização fenotípica e genotípica de amostras clínicas e indígenas de enterococcus isoladas de seres humanos: diversidade, virulência e resistência a drogas antimicrobianas - Samir de Deus Elian Andrade (2018)
Enterococci are members of the indigenous intestinal microbiota of human beings and other animals but have been emerged as nosocomial pathogens of growing relevance due to several properties such as persistence in hospital environment, easy dissemination, and resistance to several antimicrobial agents. They are intrinsically resistant to several antimicrobial drugs and demonstrate prowess to acquire additional resistance markers. In the last years, increasing frequency of bloodstream infections (BSI) has been observed and those associated with Enterococcus spp. seem to display higher mortality rates. They are also associated to community urinary tract infection (UTI). Thus, data generated from the analysis of pathogenicity and antimicrobial susceptibility profile may support the control of the microorganism spread. In this investigation, we addressed the identification and evaluated phenotypically and genotypically pathogenicity traits and the susceptibility profile to antimicrobial drugs of 103 enterococci strains isolated from 3 groups: healthy individuals (HI; n=33), UTI (n=35), and BSI (n=35). We observed the predominance of E. faecium in HI, although in UTI and BSI groups, E. faecalis was the predominant species. Typing the isolates by (GTG)5-PCR and using 90% similarity generated five different clusters, with relative efficiency in grouping the isolates according to their origin. Almost 40% of the clinical isolates (UTI and BSI) were able to produce gelatinase and almost 30% (UTI) e 40% (BSI) produced citolysin - only eight of the 103 samples expressed both enzymes. Biofilm production was assessed, and the majority of the strains were classified as non-producers, but the UTI group showed approximately 50% of producer isolates. Susceptibility test to different antimicrobial drugs were performed and considering all the studied isolates, almost 70% of the tests were classified as susceptible; it should be highlighted that in the BSI group, almost 50% of the tests showed resistance. The higher susceptibility rates (>90%) were observed to ampicillin (AMP), linezolid (LZD), and penicillin G (PEN) and the higher resistance rates were observed to ciprofloxacin (CIP, 62%), erythromycin (ERI, 77%), and tetracycline (TET, 45%). We also observed that, five among the 103 studied isolates were classified as susceptible, 24 as VRE, and 46 as multidrug-resistant. We did not observe the presence of class 1 or 2 integrons in the studied strains. Therefore, the result showed a notable difference in the prevalence of enterococci species, pathogenicity and resistance profile among the three studied groups. Furthermore, we detected a predominance of susceptibility to AMP, LZD, and PEN, as well as resistance to CIP, ERI, and TET in all groups